Post-Discharge Antibiotic Therapy in Patients with Acute Bacterial Skin and Skin Structure Infections. (4th October 2017) - Caffrey, Aisling; Beganovic, Maya; Lopes, Vrishali; LaPlante, Kerry
Abstract: Background: There are limited published data regarding the post-discharge treatment epidemiology for most infections, including acute bacterial skin and skin structure infections (ABSSSIs). Methods: This is a national descriptive study of Veterans Affairs medical center admissions with diagnosis codes for ABSSSIs between January 1, 2005 and September 30, 2015. Patients receiving vancomycin during this admission were selected for inclusion. Treatment approaches after hospital discharge, including oral antibiotics, as well as intravenous (IV) medications administered in an outpatient clinic were assessed. Differences between oral and IV groups were assessed with χ 2 or Wilcoxon tests as appropriate. Results: Of the 118, 135 ABSSSI admissions, 114, 352 (96.8%) patients continued antibiotic therapy after discharge. Most patients (98.5%) continued on oral therapy (median length of stay 4 days vs 6 days in IV group; P < 0.05). The most common oral therapies after discharge were sulfamethoxazole/trimethoprim ( n = 30, 220, 26.8%) and amoxicillin clavulanate ( n = 21, 819, 19.4%). The most common IV antibiotics were vancomycin ( n = 740, 57.5%) and ceftriaxone ( n = 220, 17.1%). Significant differences in demographics and comorbidities were observed between the oral and IV groups; however, absolute differences were negligible in some cases (e.g., median age 61 in oral group and 62 in IV group). Cultures were taken in less than half of patients (37.9% oral, 49.7% IV; P < 0.05), of which most were Staphylococcus aureus (81.7% oral, 78.4% IV; P < 0.05), with higher methicillin resistance in the IV group (59.1% oral, 63.7% IV; P < 0.05). In unadjusted comparisons between the oral and IV groups, the following 30-day outcomes differed significantly ( P < 0.05): emergency room visit (21.6% oral, 45.3% IV), readmission (13.8% oral, 25.5% IV), and reinfection (45.7% oral, 54.3% IV). Conclusion: Most patients with ABSSSI admissions continued antibiotic therapy after discharge, with only 1.1% receiving IV antibiotics in an outpatient clinic after discharge. Demographic characteristics and comorbidity burden were similar between the oral and IV groups; however, small absolute differences were statistically significant as this was a large cohort. Disclosures: A. Caffrey, Merck: Grant Investigator, Research grant. The Medicines Company: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. K. LaPlante, Merck: Grant Investigator, Grant recipient. Pfizer: Grant Investigator, Grant recipient. Cempra: Scientific Advisor, Consulting fee. The Medicines Company: Grant Investigator, Grant recipient. Allergan: Scientific Advisor, Consulting fee. Bard/ Davol: Scientific Advisor, Consulting fee. Ocean Spray: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient. Zavante: Scientific Advisor, Consulting fee. Achaogen: Scientific Advisor, Consulting fee